ASSESSMENT OF ANXIETY BEHAVIORS IN EXAMS. APLICATION DATA AND FIABILITY OF CAEX QUESTIONNAIRE - Valero Aguayo, Luis (Anales de Psicología / Annals of Psychology, 1999)
A questionnaire for the assessment of anxiety behaviors in exams is presented. The data are been obtained of university students, just before carrying out the probes. Physiological, cognitive, behavioral responses, and different types of exams or tests are self-reported. Data about groups, items, reliability, and differences between the scales of frequency and anxiety are presented.